Akuntabilitas dan Sistem Pengendalian Internal sebagai Determinan Kinerja Pegawai: Efek Moderasi Budaya Organisasi - Kathleen Asyera Risakotta; Sri Sundari; Mediaty Mediaty (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the influence of accountability, internal control systems (ISCs), and organizational culture on employee performance in the Maluku Government's Regional Apparatus Organizations (OPDs). The test results indicate that accountability (H1) has a significant positive effect on employee performance. The internal control system (H2) is also proven to have a significant effect. Organizational culture (H3) has a significant positive effect on employee performance. However, the test results show that organizational culture does not moderate the relationship between accountability and performance (H4), nor between ISCs and performance (H5). This indicates that accountability and ISCs are more dominant as technical factors than organizational culture as a moderating factor. Overall, this study confirms that accountability, ISCs, and organizational culture are important determinants of employee performance, although the moderating role of organizational culture was not significantly detected.